A Corpus-Based Study of Nominalization as a Feature of Translator’s Style (Based on the English Versions of Hong Lou Meng) - Hou, Yu (Meta)

(untitled) (Les Presses de l’Université de Montréal, 2013)
This article reports on a descriptive and explanatory study of nominalization as a feature of translators’ styles in two English versions of the Chinese novel Hong Lou Meng. This study follows Lees in defining English nominalization as a nominalized transformation of a finite verbal form, associated with the manifestation of implicitation in translation. It uses Mathesius’ complex condensation to describe English nominalization from the perspective of the sentence as adverbial, subject, and object, condensing finite clausal structures. Based on a combined quantitative and qualitative analysis, it is argued that nominalization is a feature of Joly’s formal style and a feature of Yang and Yang’s concise style. This article concludes by proposing possible interpretations of the translators’ different uses of nominalization.